A comparative study of law and practice of arbitration in Kenya, Nigeria and Zimbabwe, with particular reference to current problems in Kenya - Torgbor, Edward Nii Adja (Stellenbosch : Stellenbosch University, 2013)
Thesis (LLD)--Stellenbosch University, 2013.